Prostitution in socialist Yugoslavia: from Stalinism to the Yugoslav way. Issue 2 (4th March 2022) - Simic, Ivan
ABSTRACT: This article explores how Yugoslav communists formulated their ideas about prostitution, and how these ideas informed their approach towards sex workers. Yugoslav communists' attitudes towards prostitution were a complex combination of Stalinist gender policies, the Partisan experience of the Second World War, and attempts to find a Yugoslav path following conflict with the Soviet Union. The first postwar Yugoslav laws closely resembled Soviet models of the 1930s, but transferring a Soviet approach also meant adaptation for the Yugoslav setting. Yugoslav communists expected prostitution to disappear after the revolution and introduced harsh measures to punish sex workers. These punishments included forced labour, detainment in centres of 're-education' and expulsion from their hometowns. Broader changes in attitudes towards women's sexuality, however, led to a more lenient approach in the 1950s. The state opted to abolish labour colonies, 're-education' centres and harsh administrative measures, but prostitution remained illegal. Finally, this article examines how prostitution was depicted in films, often the only platform within which sex workers were visible.